Pengaruh Harga dan Promosi Penjualan Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Loyalitas Pelanggan Di Indogrosir Malang - Ismail, Niccolas Akbar; Nurhidayah, Nurhidayah; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of pricing and sales promotions on customer satisfaction and its impact on customer loyalty at Indogrosir Malang. Amid rising competition in the modern retail sector, understanding effective marketing strategies is essential, especially in wholesale businesses. The research uses a descriptive qualitative approach, collecting data through in-depth interviews, observation, and documentation. Informants include Indogrosir customers from various membership tiers (blue, red, black) and an internal merchandising staff member. Findings reveal that pricing significantly affects satisfaction, particularly through tiered and membership-based pricing, which customers perceive as competitive and fair. Sales promotions—such as discounts, gifts, and loyalty programs like IGR point redemption—also positively influence customer interest and satisfaction. High satisfaction leads to loyalty, seen in repeat purchases, customer recommendations, and continued patronage. The study concludes that effective pricing and targeted promotional strategies, along with consistent service quality, play a crucial role in building satisfaction and loyalty. It recommends that Indogrosir regularly evaluate its pricing and tailor promotions to customer segments to remain responsive to market changes. Keywords: Price, Sales Promotion, Customer Satisfaction, Customer Loyalty, Indogrosir.